Analisis Kualitas Layanan Jaringan Internet di Cv. Asri Jaya Mandiri dengan Metode QoS (Quality Of Service) - Muhammad Ridwan; Goldie Gunadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze the quality of internet service at CV. Asri Jaya Mandiri using the Quality of Service (QoS) and SERVQUAL methods. QoS measures network performance based on parameters such as throughput, delay, jitter, and packet loss, while SERVQUAL evaluates employees' perceptions and expectations across five dimensions: tangible, reliability, responsiveness, assurance, and empathy. The analysis reveals significant gaps, particularly in reliability and empathy, with unstable connections and inadequate access speed being the primary issues. To improve Service Quality, the study recommends infrastructure upgrades, increased bandwidth, and enhanced communication within the IT team. Implementing these measures is expected to ensure smooth operations, improve employee satisfaction, and enhance the company’s competitiveness.